Enhancement of binding affinity of anti-hapten polyclonal IgG recognizing mitragynine using affinity purification - Mustafa, Radhiahtul Raehan; Sukor, Rashidah; Mohd Nor, Siti Mariam; Saari, Nazamid; Mustaffa Kamal, Farina; Mohsin, Aliah Zannierah (Universiti Putra Malaysia Press, 2021)
Antibodies are glycoproteins found in peritoneal fluid, serum, and blood. The antibody-based assay has been used for broad applications such as immunodiagnostic and other biomedical applications. Depending on the intended application, a highly purified polyclonal antibody could be used as an alternative. Purification of antibodies from anti-sera has been proven as one of the methods to enhance the binding affinity of antibodies towards its antigen. We report herein the enhancement of the binding affinity of anti-hapten polyclonal IgG recognizing mitragynine using affinity purification. Serum from the terminal bleed of New Zealand White (NZW) rabbits immunized with mitragynine conjugated with cationized– bovine serum albumin at methyl ester (C22-MG-cBSA), or aromatic ether modification (C9-MG-cBSA) were subjected to HiTrap Protein G affinity purification using fast protein liquid chromatography (FPLC). The elution peak from chromatography fractions was analyzed using sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDSPAGE) and Western blot. Here, we report the binding of polyclonal antibodies produced from inoculation of either C22-MG-cBSA or C9-MG-cBSA immunogens of which mitragynine-ovalbumin (MG-OVA) was used as coating antigen in the ELISA assay. Non purified anti-sera from C22-MG-CBSA- inoculated rabbits showed higher titer than C9-MG-cBSA at 1/128 000 and 1/32 000 dilutions, respectively. The affinity of purified poly-IgGs from rabbits immunized with C22-MG-cBSA showed a mean Kd value of 7.965 × 10-6 µM, which was lower than those immunized with C9-MG-cBSA at mean Kd of 1.390 × 10-4 µM. In addition, the purified polyIgGs showed higher binding towards MG-OVA than non-purified anti-sera at comparable protein concentrations. These results indicated that the higher binding affinity of purified polyclonal IgG is due to the reduced competition among polyclonal antibodies with nonIgG proteins that co-existed in the non-purified anti-sera after the affinity purification.